Retrospective evaluation of implementation of caring contacts for youth suicide prevention in an emergency department - Sabrina Schalley; Kristi M. Goldenstein; Trisha Graeve; Zebulon Timmons; Nadia Elshami; Rinad S. Beidas; Jennifer A. Hoffmann (Journal of the American College of Emergency Physicians Open)
Abstract Objective Caring Contacts are brief caring messages sent to patients with suicidal thoughts or behaviors after an emergency department (ED) visit or hospitalization, which may decrease subsequent suicide attempts. We aimed to retrospectively evaluate the implementation of Caring Contacts in a children's hospital ED. Methods We conducted a retrospective observational study to evaluate the implementation of Caring Contacts within routine clinical care at an academic children's hospital ED from May 2020 to April 2023. Patients 5‒18 years old presenting for suicidal thoughts or behaviors were eligible to receive six handwritten cards with individualized caring messages, mailed over 12 months. We assessed enrollment rates (the percentage of patients offered Caring Contacts who agreed to receive them), fidelity to the intended schedule and card writer, return visits for suicidal ideation or behaviors while receiving Caring Contacts, and program costs. Results Of 627 encounters eligible for and offered Caring Contacts, 614 (98%) resulted in enrollment. Among instances of enrollment, 587 (96%) had cards sent per the intended schedule and 541 (88%) had cards written by the intended writer. A return ED visit for suicidal ideation or behaviors occurred for 168 (27%) during program participation. Costs per participant were $4.54 in materials and 0.9 h of personnel time. Conclusion In a children's hospital ED, Caring Contacts were feasible to implement with low costs and high fidelity to the intended schedule and card writer. Prospective studies are needed to assess Caring Contacts’ effectiveness in reducing suicide risk among adolescents following an ED visit.